Features of Cardiopulmonary Bypass in Mininvasive Multivessel Coronary Artery Bypass Grafting - V. M. Demianenko; O. D. Babliak; D. Y. Babliak; O. S. Stohov; E. A. Melnyk; K. A. Revenko; L. V. Pidgaina (Ukrainian Journal of Cardiovascular Surgery, 2019)
Aim. Describe the main structural and technical features of cardiopulmonary bypass in miniinvasive multivessel coronary artery bypass grafting and analyze the impact of these features on intraoperative and postoperative parameters.Materials and methods. For the period from June 2017 to April 2018, 91 patients with coronary heart disease underwent surgical intervention in our institution according to the technique of minimally invasive multivessel coronary artery bypass grafting. In order to analyze the influence of ante-retrograde autologous filling of the CPB circuit, patients undergoing miniinvasive multivessel coronary artery bypass grafting were divided into two groups: group A (without the use of this technique) and group B (with use of this technique). The groups were compared in terms of a number of intraoperative and postoperative parameters.Results. Evaluation of intraoperative parameters showed that the use of blood components was statistically significantly less in the group of patients with ante-retrograde autologous filling compared with the group without the use of this technique. In the postoperative period, the groups had statistically significant differences in the level of exudation, duration of mechanical ventilation, the length of stay in the intensive care unit and duration of hospitalization.Conclusions. The introduction of ante-retrograde autologous filling technique makes it possible to minimize the use of blood components at the intraoperative and postoperative stages, to decrease the time of mechanical ventilation, the length of stay in the intensive care unit and duration of hospitalization.